A modified space vector PWM for Bi-directional Z-source inverter - Ali, U S; Kamaraj, V (2011 International Conference on Emerging Trends in Electrical and Computer Technology, 2011)
In this paper a novel modified space vector pulse width modulation (SVPWM) technique for bidirectional Z-source inverter is presented. The approach of PWM method is different here because of the additional switch present in the input side as compared to the basic version of Z-source inverter. In the proposed modified SVPWM the shoot-through states are evenly assigned to each phase within zero state. So zero voltage period is diminished for generating a shoot-through time, and active states are unchanged. Simulation and experimental results are presented to demonstrate the new features.